Effects of tuning the applied voltage pulse periods on the electroluminescence spectra of host–guest white light-emitting electrochemical cells. Issue 27 (25th June 2018) - Wu, Ming-Lun; Chen, Guan-Yu; Shih, Ting-An; Lu, Chin-Wei; Su, Hai-Ching
Abstract : Tunable correlated color temperature of electroluminescence from white light-emitting electrochemical cells based on adjusting the voltage pulse period. Abstract : Solid-state white light-emitting electrochemical cells (LECs) are potential candidates in solid-state lighting due to their promising advantages of simple device structure, low-voltage operation and compatibility with inert cathode metals. Adjusting the correlated color temperature (CCT) of background illumination is highly desired for modern smart lighting systems. In this work, a novel technique to tune the CCT of electroluminescence (EL) from white LECs is proposed. Color tuning is based on adjusting the applied voltage pulse period on the host–guest white LECs and the working mechanism is illustrated. A shorter voltage pulse period is insufficient to completely charge the capacitive LEC device and thus the effective voltage applied on the device is lower. Since the host–guest energy level offsets favor carrier trapping, a lower effective applied voltage results in a more pronounced guest emission, rendering redder white EL with a lower CCT. On the other hand, a longer voltage pulse period facilitates more complete charging and the effective voltage applied on the white LEC is higher. A higher bias facilitates direct exciton formation on the host molecule and subsequent partial host–guest energy transfer generates bluer white EL with a higher CCT. By tuning the voltage pulse period from 0.2 to 20 ms, the CCT of EL resulting from white LECs ranges from 2482 to 5723 K. The CCT tuning range is sufficient for general lighting applications. In contrast to color tuning of white LECs under constant-voltage driving, in which >10× brightness enhancement is accompanied by higher-CCT white EL, the discharging half-period in pulse-voltage driving provides relaxation time to turn off the device and reduces the average brightness of the white LECs driven under a longer voltage pulse period. Therefore, similar brightness can be achieved for white EL with different CCTs. No additional optical filtering device is needed for this novel color tuning technique and it has potential for use in solid-state lighting.